Proximal Hamstring Tendinopathy: A Systematic Review of Interventions - Anthony Michael Nasser; Bill Vicenzino; Alison Grimaldi; Jay Anderson; Adam Ivan Semciw (International Journal of Sports Physical Therapy)
# Background Proximal hamstring tendinopathy affects athletic and non-athletic populations and is associated with longstanding buttock pain. The condition is common in track and field, long distance running and field-based sports. Management options need to be evaluated to direct appropriate clinical management.